Ecophysiological traits in C3 and C4 grasses a phylogenetically controlled screening experiment - Taylor, Samuel H (The New phytologist, 2010)
Experimental evidence demonstrates a higher efficiency of water and nitrogen use in C(4) compared with C(3) plants, which is hypothesized to drive differences in biomass allocation between C(3) and C(4) species. However, recent work shows that contrasts between C(3) and C(4) grasses may be misinterpreted without phylogenetic control. Here, we compared leaf physiology and growth in multiple lineages of C(3) and C(4) grasses sampled from a monophyletic clade, and asked the following question: which ecophysiological traits differ consistently between photosynthetic types, and which vary among lineages? C(4) species had lower stomatal conductance and water potential deficits, and higher water-use efficiency than C(3) species. Photosynthesis and nitrogen-use efficiency were also greater in C(4) species, varying markedly between clades. Contrary to previous studies, leaf nitrogen concentration was similar in C(4) and C(3) types. Canopy mass and area were greater, and root mass smaller, in the tribe Paniceae than in most other lineages. The size of this phylogenetic effect on biomass partitioning was greater in the C(4) NADP-me species than in species of other types. Our results show that the phylogenetic diversity underlying C(4) photosynthesis is critical to understanding its functional consequences. Phylogenetic bias is therefore a crucial factor to be considered when comparing the ecophysiology of C(3) and C(4) species